An exploration of the relational well-being of African international students at a South African university - Letsoalo, T. S.; Chigeza, S.; Wilson Fadiji, A. (South African Journal of Higher Education, 2024)
International students are susceptible to threats to their well-being, as their immigrant status in host societies exposes them to unique challenges such as language difficulties, cultural differences, social isolation, and discrimination (to list a few). Relationships are an important component of individuals’ well-being that can mitigate these challenges. Hence, this study aimed to explore the experiences of relational well-being of African international students at a South African university. The study adopted a qualitative design wherein semi-structured interviews were employed to collect data from 16 participants (mean age = 24; females = 5; males = 11). Using thematic analysis, we found that African international students have reciprocal positive relationships with local and other immigrant students, and these contribute to well-being outcomes in the social, psychological, and educational domains of life. In addition, the prevailing institutional culture and the availability of spaces that provide opportunities for interaction are important determinants of relational experiences in the university campus space. It is recommended that student affairs departments create spaces in which African international students could further engage and interact with a diverse group of students to enhance their relational well-being.